2007
DOI: 10.1136/jcp.2007.050666
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α expression correlates with focal macrophage infiltration, angiogenesis and unfavourable prognosis in urothelial carcinoma

Abstract: Our results indicate that HIF-1alpha is a key regulator of the angiogenic cascade. We show that HIF-1alpha is an independent prognostic factor for disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 23 publications
2
66
1
Order By: Relevance
“…Our results are parallel to the studies in the literature regarding the correlation between HIF-1a and clinicopathologic parameters in urothelial carcinomas [9][10][11][12]. Eltz et al suggested that HIF-1a is significantly associated with the grade and pattern of growth in urothelial carcinomas of the upper urinary tract [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are parallel to the studies in the literature regarding the correlation between HIF-1a and clinicopathologic parameters in urothelial carcinomas [9][10][11][12]. Eltz et al suggested that HIF-1a is significantly associated with the grade and pattern of growth in urothelial carcinomas of the upper urinary tract [11].…”
Section: Discussionsupporting
confidence: 92%
“…A strong relationship between HIF-1a immunoreactivity and the grade of the tumor in bladder urothelial carcinomas was claimed [9][10][11][12]. In our study the relation between HIF-1a immunoreactivity and the grade of the tumor was statistically significant (P = 0.002).…”
Section: Discussionsupporting
confidence: 42%
“…BTCC is one of the common solid tumors with low oxygen tension because rapid tumor growth outstrips the capability of existing blood vessels to supply oxygen, and hyp oxic regions commonly occur. It has been reported that overexpression of HIF-1 ␣ is common in BTCC, and it is an independent prognostic factor for disease-free survival [10,21] . Thus, the blockade of HIF-1 ␣ appears to be a promising strategy for the treatment of metastatic BTCC.…”
Section: Discussionmentioning
confidence: 99%
“…Under normoxic conditions, HIF-1α mRNA is translated, but its protein is rapidly degraded (11 prevented, facilitating the regulation of the expression of a series of genes, which are involved in cell proliferation, differentiation, apoptosis, angiogenesis, migration and invasion (12). The overexpression of HIF-1α has been identified in patients with bladder carcinoma, and the expression of HIF-1α is correlated with the progression and recurrence of bladder carcinoma (13). Consequently, in addition to being a diagnostic biomarker, HIF-1α may be a novel therapeutic target in bladder carcinoma.…”
Section: Introductionmentioning
confidence: 99%